Utilization Of Sugarcane Filter Cake to Reduce The Use of Cement in Brick Making - Andri Fernando Pakpahan; Ainun Rohana; Sulastri Panggabean (Universitas Sumatera Utara, 2015)
Sugarcane filter cake can be used in brick-making to reduce the use of cement.The size, compressive strength and absorption was calculated. This research used non-factorial completely random used design with filter cake level (A) consisted of three types i.e (A1= 5%, A2= 15%, A3= 25%). The parameters was size, compressive strength and absorption. The result showed that sugarcane filter percentage had significant effect on size, compressive strength and absorption. The highest measure was at level 25% and the lowest was at filter cake of 5%. The highest compressive strength value obtained at 5% level of filter cake and lowest value obtained at 25% filter cake. The highest absorption filter cake was obtained at 25% and the lowest was at 5% level. Keywords: Brick, Filter Cake, Waste.